Coping Strategies and Anxiety Among Maritime Students Before Sea Practice - Aqila Nadra Rabbani; Zunaina Zamhariri; Sierra Sinta Sunarso Putri (International Conference on Psychology and Education (ICPE), 2025)
This qualitative study investigates the coping strategies utilized by Indonesian maritime students to manage anxiety prior to sea practice. Data were collected through semi-structured interviews, observations, and reflective journals from purposively selected student. Thematic analysis revealed that relaxation techniques, problem-focused preparation, social support, and distraction methods are predominant coping mechanisms employed to reduce anxiety and enhance readiness. The findings highlight the importance of strengthening psychological and social support systems within maritime education institutions to foster student resilience and performance during practical sea training. Recommendations include integrating coping skills training into curricula and involving families to optimize student mental health. A phenomenological case study approach was employed, with data collected through semi-structured interviews, direct observations during simulated training, and reflective journals from one purposively selected maritime student from Surabaya Polytechnic. The participant was chosen based on high anxiety levels and active engagement in preparatory activities. Thematic analysis following Braun and Clarke's framework was used to identify patterns and themes in the data.